Obstetric Nursing Intervention Models for Hypertensive Disorders of Pregnancy and Their Effect Evaluation - Huang, Shangzhuan (Pacific International Journal, 2025)
This study evaluated the effectiveness of different obstetric nursing intervention models for Hypertensive Disorders of Pregnancy (HDP). A total of 120 pregnant women with HDP were randomly assigned to a predictive (anticipatory) intervention group, a comprehensive intervention group, or a control group receiving routine care (n=40 per group). Outcomes included delivery mode, anxiety/depression scores (SAS/SDS), and adverse maternal/neonatal outcomes. The predictive intervention group demonstrated a significantly higher vaginal delivery rate (75.00%) than both the comprehensive (65.00%) and control (47.50%) groups (P<0.05). Both intervention groups showed significantly lower pre-delivery SAS and SDS scores compared to the control group (P<0.05), with no significant difference between the two intervention groups. The incidences of adverse maternal (7.50%) and neonatal (5.00%) outcomes were lowest in the predictive group, followed by the comprehensive group. In conclusion, compared to routine care, both nursing models improve psychological outcomes, but the predictive intervention model appears more effective in optimizing delivery mode and reducing clinical complications.